Nanoparticle-doped self-repairing hydrogel plugging material and preparation method thereof

By doping modified nanoparticles and gel-type hydrophobic polymers into the leak plugging material, a dual network hydrogel system is formed, which solves the problem of insufficient stability and mechanical properties of existing leak plugging materials in high temperature environments, and achieves efficient leak plugging effect.

CN119684512APending Publication Date: 2025-03-25CNPC BOHAI DRILLING ENG +2

Patent Information

Application Number
CN202311239570.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing leak-blocking materials are insufficient in high temperature environments and have poor mechanical properties, making it difficult to effectively seal the leak-blocking channels in deep strata.

Method used

A self-healing hydrogel leak plugging material doped with nanoparticles is used. This material forms a dual network hydrogel system by uniformly dispersing the modified nanoparticles in the gel-type hydrophobic polymer, which enhances the mechanical properties and temperature resistance of the gel.

Benefits of technology

Under a high temperature environment of 80℃~150℃, the material can repair itself, form a gel whole with good mechanical properties, effectively sealing the leakage channels of the formation, and improving the success rate of leakage plugging and the stability of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nanoparticle-doped self-repairing hydrogel leaking stoppage material and a preparation method thereof. The nanoparticle-doped self-repairing hydrogel leaking stoppage material is obtained by uniformly dispersing modified nanoparticles in a gel type hydrophobic association polymer, the modified nano particles are formed by modifying nano particles with acidified 3-aminopropyltriethoxysilane, and the modified nano particles are formed by modifying the nano particles with the acidified 3-aminopropyltriethoxysilane; the gel type hydrophobic associated polymer is formed by copolymerizing a hydrophobic monomer, acrylic acid and an acrylamide monomer which are dissolved in a mixed solvent; the hydrophobic monomer is at least one of lauryl methacrylate, dodecyl methacrylate, hexadecyl methacrylate, octadecyl methacrylate and methyl methacrylate; the acrylamide monomer is at least one of acrylamide and N, N-dimethyl bisacrylamide; the mixed solvent is composed of a sodium chloride solution and a surfactant; the preparation method of the nano-particle doped self-repairing hydrogel leaking stoppage material is simple, convenient and easy to implement, and the nano-particle doped self-repairing hydrogel leaking stoppage material has excellent self-repairing performance and has high pressure bearing capacity before and after self-repairing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plugging for oil drilling, and in particular to a nanoparticle-doped self-repairing hydrogel plugging material and a preparation method thereof. Background Art

[0002] Well leakage refers to the phenomenon that a large amount of drilling fluid leaks into the formation during the drilling process. It will not only cause a large amount of working fluid to be lost, directly causing significant economic losses, but also increase non-productive time, extend the drilling cycle, affect the exploration and development process, and even induce accidents such as drill sticking, well collapse, and blowout.

[0003] As exploration and development expands to deep, ultra-deep, unconventional and other resource areas, the incidence of well leakage is increasing. Traditional plugging materials and plugging methods have certain limitations in dealing with well leakage. For example, when bridge plug plugging encounters large cracks and many cracks in the leaking layer, it is difficult to form a good plugging layer around the wellbore, and false plugging is easy to occur. When cement slurry plugging encounters a lot of formation fluid, it will be diluted by the formation fluid and cannot solidify, resulting in plugging failure. Most inorganic gel plugging materials have poor viscoelasticity and poor toughness. Therefore, after entering the cracks, solidifying and breaking under force, the fragments cannot adhere to each other and cannot maintain their original state. They are easily carried away by drilling fluid and cannot effectively plug the formation. Polymer gel plugging agents have good water absorption and expansion, elastic deformation capabilities, strong deformability, are not restricted by the leakage channel when plugging, can enter the cracks and pore spaces through extrusion deformation, can better stay in the leaking layer, form a viscoelastic body to achieve the purpose of plugging, and thus effectively control malignant leakage.

[0004] Self-healing gel is a gel system formed by reversible dynamic bonds such as ionic bonds, hydrogen bonds, hydrophobic association, and DA reactions. It can spontaneously repair itself after being damaged to restore its structure and function. In addition, after entering the leakage layer, the self-healing hydrogel particles can be re-crosslinked to form a whole. After being damaged by external forces, they can also self-repair through their own internal reversible covalent / non-covalent bonds, overcoming the defects of traditional hydrogels that are easy to break in the leakage layer and have insufficient pressure bearing capacity. However, the formation of conventional self-healing hydrogels often relies on non-covalent bonds, such as hydrogen bonds, supramolecular interactions, and other intermolecular interactions, which are relatively weak and lack stability at high temperatures. Conventional self-healing hydrogels also have problems such as severe structural heterogeneity, single cross-linking mode, lack of effective energy dissipation mechanism, and poor mechanical properties.

[0005] Based on this, it is necessary to develop a self-healing gel plugging material with temperature resistance and excellent mechanical properties, so as to achieve the purpose of efficient plugging of high-temperature leakage channels. Summary of the invention

[0006] The purpose of the present invention is to provide a nanoparticle-doped self-repairing hydrogel plugging material which can achieve self-repair in a high-temperature formation environment of 80°C to 150°C and form a gel whole with good mechanical properties.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned nanoparticle-doped self-repairing hydrogel plugging material.

[0008] To this end, the technical solution of the present invention is as follows:

[0009] A nanoparticle-doped self-repairing hydrogel plugging material is obtained by uniformly dispersing modified nanoparticles in a gel-type hydrophobic associating polymer; wherein the modified nanoparticles are formed by modifying the nanoparticles with acidified 3-aminopropyltriethoxysilane, and the nanoparticles are at least one of nano-alumina powder, nano-silicon oxide powder, nano-magnesium oxide powder, nano-zirconium oxide powder, and hydrotalcite; the particle size of the nanoparticles is preferably 50nm to 120nm; the gel-type hydrophobic associating polymer is formed by copolymerizing a hydrophobic monomer, acrylic acid, and acrylamide monomers dissolved in a mixed solvent; the hydrophobic monomer is methyl At least one of lauryl acrylate, dodecyl methacrylate, hexadecyl methacrylate, octadecyl methacrylate and methyl methacrylate; the acrylamide monomer is at least one of acrylamide and N,N-dimethylbisacrylamide; the weight ratio of the hydrophobic monomer to the water in the sodium chloride solution is (1-3):70, the weight ratio of acrylic acid to the water in the sodium chloride solution is (1-2):70, the weight ratio of the acrylamide monomer to the water in the sodium chloride solution is (1.5-2.5):7, and the weight ratio of the modified nanoparticles to the water in the sodium chloride solution is (2-8):70.

[0010] The mixed solvent is composed of a sodium chloride solution and a surfactant; the surfactant is at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium tetradecyl sulfate, sodium dodecylbenzene sulfonate and octadecyltrimethylammonium bromide; the sodium chloride aqueous solution is prepared from sodium chloride and water in a weight ratio of (1-2):35; the weight ratio of the surfactant to the water in the sodium chloride solution is (1-2):18; wherein the mixed solvent is prepared for the purpose of enabling the hydrophobic monomer to be co-dissolved with acrylic acid and acrylamide monomers to achieve copolymerization, and at the same time, the sodium chloride solution in the solvent not only has the effect of reducing the critical micelle concentration (CMC) of the solution, but also can promote the continuous growth of micelles in the micelle solution, that is, the concentration of the NaCl solution is positively correlated with the growth of the micelle particle size.

[0011] A method for preparing the above-mentioned nanoparticle-doped self-repairing hydrogel plugging material comprises the following steps:

[0012] S1, dispersing 3-aminopropyltriethoxysilane in a mixed solution of ethanol and hydrochloric acid to obtain a dispersion I;

[0013] S2, filtering the dispersion I and drying the obtained solid to obtain a solid powder;

[0014] S3, dispersing the nanoparticles in a mixed solution of ethanol and water to obtain a dispersion II;

[0015] S4, slowly adding the solid powder to the dispersion II, and stirring the reaction at 40°C to 80°C for 6h to 10h to obtain a dispersion III;

[0016] S5, centrifuging the dispersion III, washing the obtained solid with a low boiling point solvent, and drying it to obtain modified nanoparticles;

[0017] S6, prepare sodium chloride aqueous solution;

[0018] S7, dissolving the surfactant, the hydrophobic monomer, the acrylic acid and the acrylamide monomer in a sodium chloride aqueous solution to obtain a monomer mixture;

[0019] S8, uniformly dispersing the modified nanoparticles in the monomer mixture to obtain a suspension;

[0020] S9, under an inert atmosphere, adding a catalyst to the suspension, and allowing the suspension to react at room temperature to 60° C. for 2 h to 6 h to obtain a self-healing gel base material;

[0021] S10, vacuum drying and crushing the self-repairing hydrogel base material to obtain the nanoparticle-doped self-repairing hydrogel plugging material.

[0022] Preferably, in step S1, the mixed solution of ethanol and hydrochloric acid is prepared by uniformly mixing ethanol in a weight ratio of (6-17):1 and 37.5wt.% of dilute hydrochloric acid; the weight ratio of 3-aminopropyltriethoxysilane to the mixed solution is (10-40):100.

[0023] Preferably, in step S1, 3-aminopropyltriethoxysilane is dispersed in a mixed solution of ethanol and hydrochloric acid by stirring, and the stirring time is 24h to 48h.

[0024] Preferably, in step S2, the obtained solid is placed at 50°C to 80°C and dried for 12h to 24h.

[0025] Preferably, in step S3, the mixed solution of ethanol and water is formed by uniformly mixing ethanol and water in a weight ratio of (1-2):1; and the weight ratio of the nanoparticles to the mixed solution is (0.5-3):20.

[0026] Preferably, in step S3, the nanoparticles are dispersed in a mixed solution of ethanol and water by ultrasound, and the ultrasonic dispersion time is 2h to 4h.

[0027] Preferably, in step S4, the weight ratio of solid powder I to dispersion liquid II is (10-30):100.

[0028] Preferably, in step S5, the low boiling point solvent is at least one of acetone, ethanol and methanol; the drying temperature is adjusted to 50°C to 80°C, and the drying time is 12h to 24h.

[0029] Preferably, in step S7, the stirring time is 6 h to 10 h.

[0030] Preferably, in step S8, the stirring time is 6 to 12 hours.

[0031] Preferably, in step S9, the inert atmosphere is formed by introducing an inert gas into the suspension at a gas flow rate of 20 mL / min to 40 mL / min for 10 min to 30 min; the inert gas is at least one of nitrogen, helium, neon and argon.

[0032] Preferably, the initiator is at least one of ammonium persulfate, sodium persulfate and potassium persulfate; the weight ratio of the initiator to all monomers is (5-8):1000.

[0033] Preferably, in step S10, the vacuum degree of vacuum drying is 0.05 MPa to 0.08 MPa, the drying temperature is 40° C. to 50° C., and the drying time is 24 h to 48 h.

[0034] Compared with the prior art, the nanoparticle-doped self-repairing hydrogel plugging material is obtained by uniformly dispersing modified nanoparticles in a gel-type hydrophobic associating polymer, and has the following beneficial effects: in the plugging material, the hydrophobic associating polymer is used as the main material, which is a hydrogel system copolymerized by hydrophobic monomers, acrylic acid and acrylamide monomers; the molecular chains of the hydrophobic associating polymer are mainly connected by the electrostatic interaction between the anions and cations on the copolymerized monomers through the completely physically cross-linked hydrophobic association (i.e., the hydrophobic monomer is dissolved in an aqueous solution containing a surfactant to form a free radical micelle cross-linking point) to form a hydrophobic associating micro-region; the hydrophobic associating micro-region not only makes the hydrogel exhibit good toughness when stretched and deformed, but also dissipates the reversible dissociation energy of the hydrophobic chains in the hydrophobic associating micro-region; at the same time, The hydrophobic associating microregion also gives the gel self-healing properties through intermolecular forces; in actual applications, after the self-healing gel enters the formation while drilling, it forms a new gel as a whole through re-crosslinking at a specific formation temperature, thereby achieving the purpose of plugging leaks, reducing the difficulty of the downhole plugging construction process and improving the success rate of plugging leaks; in addition, in the plugging material, the modified nanoparticles are modified by an acidified silane coupling agent to form abundant cationic sites on the nanoparticles, which are then connected to the carboxyl groups of the acrylic acid monomers in the gel-type hydrophobic associating polymer through electrostatic action, and then form a double-network hydrogel system with the hydrophobic associating polymer, which has the dual effects of enhancing the mechanical properties and temperature resistance of the gel, and ensures the stability of the self-healing gel plugging material in high-temperature formations. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with specific examples, but the following examples are by no means limiting the present invention in any way. The raw materials used in the examples are all conventional raw materials and can be obtained commercially; the methods described are all prior art unless otherwise specified.

[0036] Example 1

[0037] A nanoparticle-doped self-repairing hydrogel plugging material is prepared by the following steps:

[0038] S1, adding 30 parts by weight of 3-aminopropyltriethoxysilane to a mixed solution of 100 parts by weight of ethanol and 1 part by weight of 37.5 wt.% dilute hydrochloric acid, and stirring at room temperature for 2 days to obtain a dispersion I;

[0039] S2, filtering the dispersion I obtained in step S1, and drying the obtained solid in an oven at 60° C. for 12 h to obtain a solid powder;

[0040] S3. Add 15 parts by weight of nano-silicon dioxide powder (50-100 nm) to a mixed solution of 50 parts by weight of ethanol and 50 parts by weight of water, and disperse by ultrasonic for 2 hours to obtain dispersion II.

[0041] S4, slowly adding 15 parts by weight of the solid powder obtained in step S2 to the dispersion II obtained in step S3, and stirring the mixture at 80° C. for 6 hours to obtain dispersion III;

[0042] S5, centrifuging the dispersion III obtained in step S4, washing the obtained solid with ethanol three times, and drying it in an oven at 60° C. for 15 h to obtain modified nanoparticles;

[0043] S6, add 2 parts by weight of sodium chloride to 70 parts by weight of water, stir and dissolve evenly to obtain a sodium chloride aqueous solution;

[0044] S7, adding 4 parts by weight of sodium dodecyl sulfate, 1.5 parts by weight of octadecyl methacrylate, 1.5 parts by weight of acrylic acid and 18 parts by weight of acrylamide to the sodium chloride aqueous solution obtained in step S6, and stirring for 6 hours until all monomers are dissolved to obtain a monomer mixture;

[0045] S8, slowly adding 4 parts by weight of the modified nanoparticles obtained in step S5 to the monomer mixture obtained in step S7, and stirring for 6 hours to uniformly disperse the modified nanoparticles in the monomer mixture to obtain a suspension;

[0046] S9, introducing nitrogen gas into the suspension obtained in step S8 at a ventilation flow rate of 40 mL / min and bubbling for 15 min, then adding 0.15 parts by weight of ammonium persulfate, and standing for reaction at 45° C. for 4 h to obtain a self-healing gel base;

[0047] S10, drying the self-healing hydrogel base material obtained in step S9 at a temperature of 45° C. and a vacuum degree of 0.06 MPa for 48 hours to obtain a solid self-healing hydrogel base material, and crushing the solid for standby use.

[0048] Example 2

[0049] A nanoparticle-doped self-repairing hydrogel plugging material is prepared by the following steps:

[0050] S1, adding 30 parts by weight of 3-aminopropyltriethoxysilane to a mixed solution of 100 parts by weight of ethanol and 1 part by weight of 37.5 wt.% dilute hydrochloric acid, and stirring at room temperature for 2 days to obtain a dispersion I;

[0051] S2, filtering the dispersion obtained in step S1, and drying the obtained solid in an oven at 60° C. for 12 h to obtain a solid powder;

[0052] S3. Add 15 parts by weight of nano-alumina powder (50-120 nm) to a mixed solution of 50 parts by weight of ethanol and 50 parts by weight of water, and disperse by ultrasonic for 2 hours to obtain dispersion II.

[0053] S4, slowly adding 15 parts by weight of the solid powder obtained in step S2 to the dispersion II obtained in step S3, and stirring the mixture at 80° C. for 6 hours to obtain dispersion III;

[0054] S5, centrifuging the dispersion III obtained in step S4, washing the obtained solid with ethanol three times, and drying it in an oven at 60° C. for 15 h to obtain modified nanoparticles;

[0055] S6, add 2 parts by weight of sodium chloride to 70 parts by weight of water, stir and dissolve evenly to obtain a sodium chloride aqueous solution;

[0056] S7, adding 4 parts by weight of sodium dodecyl sulfate, 1.5 parts by weight of octadecyl methacrylate, 1.5 parts by weight of acrylic acid and 18 parts by weight of acrylamide to the sodium chloride aqueous solution obtained in step S6, and stirring for 6 hours until all monomers are dissolved to obtain a monomer mixture;

[0057] S8, slowly adding 4 parts by weight of the modified nanoparticles obtained in step S5 to the monomer mixture obtained in step S7, and stirring for 6 hours to uniformly disperse the modified nanoparticles in the monomer mixture to obtain a suspension;

[0058] S9, introducing nitrogen gas into the suspension obtained in step S8 at a ventilation flow rate of 40 mL / min and bubbling for 15 min, then adding 0.15 parts by weight of ammonium persulfate, and standing for reaction at 45° C. for 4 h to obtain a self-healing gel base;

[0059] S10, drying the self-healing hydrogel base material obtained in step S9 at a temperature of 45° C. and a vacuum degree of 0.06 MPa for 48 hours to obtain a solid self-healing hydrogel base material, and crushing the solid for standby use.

[0060] Example 3

[0061] A nanoparticle-doped self-repairing hydrogel plugging material is prepared by the following steps:

[0062] S1, adding 30 parts by weight of 3-aminopropyltriethoxysilane to a mixed solution of 100 parts by weight of ethanol and 1 part by weight of 37.5 wt.% dilute hydrochloric acid, and stirring at room temperature for 2 days to obtain a dispersion I;

[0063] S2, filtering the dispersion obtained in step S1, and drying the obtained solid in an oven at 60° C. for 12 h to obtain a solid powder;

[0064] S3. Add 15 parts by weight of nano-alumina powder (50-120 nm) to a mixed solution of 50 parts by weight of ethanol and 50 parts by weight of water, and disperse by ultrasonic for 2 hours to obtain dispersion II.

[0065] S4, slowly adding 15 parts by weight of the solid powder obtained in step S2 to the dispersion II obtained in step S3, and stirring the mixture at 80° C. for 6 hours to obtain dispersion III;

[0066] S5, centrifuging the dispersion III obtained in step S4, washing the obtained solid with ethanol three times, and drying it in an oven at 60° C. for 15 h to obtain modified nanoparticles;

[0067] S6, add 2 parts by weight of sodium chloride to 70 parts by weight of water, stir and dissolve evenly to obtain a sodium chloride aqueous solution;

[0068] S7, adding 4 parts by weight of sodium dodecyl sulfate, 1.5 parts by weight of lauryl methacrylate, 1.5 parts by weight of acrylic acid and 18 parts by weight of acrylamide to the sodium chloride aqueous solution obtained in step S6, and stirring for 6 hours until all monomers are dissolved to obtain a monomer mixture;

[0069] S8, slowly adding 4 parts by weight of the modified nanoparticles obtained in step S5 to the monomer mixture obtained in step S7, and stirring for 6 hours to uniformly disperse the modified nanoparticles in the monomer mixture to obtain a suspension;

[0070] S9, introducing nitrogen gas into the suspension obtained in step S8 at a ventilation flow rate of 40 mL / min and bubbling for 15 min, then adding 0.15 parts by weight of ammonium persulfate, and standing for reaction at 45° C. for 4 h to obtain a self-healing gel base;

[0071] S10, drying the self-healing hydrogel base material obtained in step S9 at a temperature of 45° C. and a vacuum degree of 0.06 MPa for 48 hours to obtain a solid self-healing hydrogel base material, and crushing the solid for standby use.

[0072] Comparative Example 1

[0073] A gel plugging material is prepared by the following steps:

[0074] S1, add 2 parts by weight of sodium chloride to 70 parts by weight of water, and stir to dissolve evenly to obtain a sodium chloride aqueous solution;

[0075] S2, adding 4 parts by weight of sodium dodecyl sulfate, 1.5 parts by weight of lauryl methacrylate, 1.5 parts by weight of acrylic acid and 18 parts by weight of acrylamide to the sodium chloride aqueous solution obtained in step S1, and stirring for 6 hours until all monomers are dissolved to obtain a monomer mixture;

[0076] S3, slowly adding 4 parts by weight of nano-silicon dioxide (50-100 nm) to the monomer mixture obtained in step S2, and stirring for 6 hours to uniformly disperse the nano-silicon dioxide in the monomer mixture to obtain a suspension;

[0077] S4, introducing nitrogen gas into the suspension obtained in step S3 at a ventilation flow rate of 40 mL / min and bubbling for 15 min, then adding 0.15 parts by weight of ammonium persulfate, and standing for reaction at 45° C. for 4 h to obtain a base material;

[0078] S5. Dry the self-repairing hydrogel base material obtained in step S9 at a temperature of 45° C. and a vacuum degree of 0.06 MPa for 48 hours to obtain a solid plugging material, and crush the solid for standby use.

[0079] Comparative Example 2

[0080] A gel plugging material is prepared by the following steps:

[0081] S1, add 2 parts by weight of sodium chloride to 70 parts by weight of water, and stir to dissolve evenly to obtain a sodium chloride aqueous solution;

[0082] S2, adding 4 parts by weight of sodium dodecyl sulfate, 1.5 parts by weight of lauryl methacrylate, 1.5 parts by weight of acrylic acid and 18 parts by weight of acrylamide to the sodium chloride aqueous solution obtained in step S1, and stirring for 6 hours until all monomers are dissolved to obtain a monomer mixture;

[0083] S3, introducing nitrogen gas into the suspension obtained in step S3 at a ventilation flow rate of 40 mL / min and bubbling for 15 min, then adding 0.15 parts by weight of ammonium persulfate, and standing for reaction at 45° C. for 4 h to obtain a base material;

[0084] S4, drying the self-repairing hydrogel base material obtained in step S9 at a temperature of 45° C. and a vacuum degree of 0.06 MPa for 48 hours to obtain a solid plugging material, and crushing the solid for standby use.

[0085] Comparative Example 3

[0086] A gel plugging material is prepared by the following steps:

[0087] S1, adding 30 parts by weight of 3-aminopropyltriethoxysilane to a mixed solution of 100 parts by weight of ethanol and 1 part by weight of hydrochloric acid, and stirring at room temperature for 2 days to obtain a dispersion I;

[0088] S2, filtering the dispersion obtained in step S1, and drying the obtained solid in an oven at 60° C. for 12 h to obtain a solid powder;

[0089] S3. Add 15 parts by weight of nano-silicon dioxide powder (50-100 nm) to a mixed solution of 50 parts by weight of ethanol and 50 parts by weight of water, and disperse by ultrasonic for 2 hours to obtain dispersion II.

[0090] S4, slowly adding 15 parts by weight of the solid powder obtained in step S2 to the dispersion II obtained in step S3, and stirring the mixture at 80° C. for 6 hours to obtain dispersion III;

[0091] S5, centrifuging the dispersion III obtained in step S4, washing the obtained solid with ethanol three times, and drying it in an oven at 60° C. for 15 h to obtain modified nanoparticles;

[0092] S6, add 2 parts by weight of sodium chloride to 70 parts by weight of water, stir and dissolve evenly to obtain a sodium chloride aqueous solution;

[0093] S7, adding 4 parts by weight of sodium dodecyl sulfate, 1.5 parts by weight of acrylic acid and 18 parts by weight of acrylamide to the sodium chloride aqueous solution obtained in step S6, and stirring for 6 hours until all monomers are dissolved to obtain a monomer mixture;

[0094] S8, slowly adding 4 parts by weight of the modified nanoparticles obtained in step S5 to the monomer mixture obtained in step S7, and stirring for 6 hours to uniformly disperse the modified nanoparticles in the monomer mixture to obtain a suspension;

[0095] S9, introducing nitrogen gas into the suspension obtained in step S8 at a ventilation flow rate of 40 mL / min and bubbling for 15 min, then adding 0.15 parts by weight of ammonium persulfate, and standing for reaction at 45° C. for 4 h to obtain a base material;

[0096] S10, drying the self-repairing hydrogel base material obtained in step S9 at a temperature of 45° C. and a vacuum degree of 0.06 MPa for 48 hours to obtain a solid plugging material, and crushing the solid for standby use.

[0097] Performance Test:

[0098] The performance tests of the plugging materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are as follows:

[0099] (I) Pressure bearing performance test:

[0100] After the plugging material and the plugging base slurry are mixed evenly, the plugging slurry is obtained. The test uses a horizontal flow pump to inject the plugging slurry into the metal seam plate (the length of the seam plate is 12.5cm, and the inlet and outlet crack widths are 3mm and 1mm respectively) at a flow rate of 5mL / min; then, the metal seam plate is placed in an aging tank filled with 20mL bentonite slurry, and kept warm at the specified experimental temperature for 12h, and the metal seam plate is taken out from the aging tank for pressure bearing capacity test. Among them, the plugging slurry is prepared by adding 10 parts by weight of plugging materials to 100 parts by weight of plugging base slurry and mixing them evenly; the plugging base slurry is prepared by slowly adding 5 parts by weight of bentonite and 0.25 parts by weight of sodium carbonate to 100 parts by weight of water, and each time a raw material is added to the water, a high-speed stirrer is used to stir at a stirring speed of 10000rpm for 10min until the raw materials are evenly dispersed. After the addition is completed, continue stirring for 24h to obtain a water-based drilling fluid base slurry. The pressure bearing performance test is specifically completed by a leak-proof instrument. The test method is: place the seam plate in the clamp, open the liquid outlet valve, inject 2L of bentonite slurry into the container, set the displacement pressure to 0.5MPa, and increase it by 0.5MPa every 2 minutes until the liquid continues to flow out of the outlet. At this time, the maximum pressure at this moment is the pressure bearing capacity of the sample.

[0101] (ii) Tensile breaking stress test:

[0102] The tensile fracture stress test was specifically completed using a universal testing machine. The test method was as follows: the prepared solid self-healing gel base material was cut into a rectangular shape with a length of 40 mm ± 2 mm, a width of 15 mm ± 2 mm, and a thickness of 5 mm ± 2 mm. The stretching rate was set to 50 mm / min, and the distance between the two clamps was set to 30 mm. The maximum fracture stress and strain of the hydrogel were obtained through the tensile stress-strain curve.

[0103] (III) Self-repair capability test:

[0104] The prepared solid self-healing gel base was cut into gels with a diameter of 1 cm, and a section of the gel in the cylinder was cut and its initial length was recorded as L0; then, the gel was cut in the middle, the two parts of the gel sample were spliced ​​together along the original cross section, wrapped with plastic wrap and placed in an oven at a specified experimental temperature for 4 hours for self-healing; the healed gel was placed at room temperature and its length L when stretched to break was tested y , using the formula:

[0105] θ=(L y / L0)×100%, and the healing rate θ is calculated.

[0106] The following Table 1 shows the performance test results when the experimental temperature is specified to be 120°C; the following Table 2 shows the performance test results when the experimental temperature is specified to be 150°C.

[0107] Table 1:

[0108] Test Case Pressure bearing capacity / MPa Tensile breaking stress / kPa Healing rateθ Example 1 5.5 14.3 506% Example 2 4.5 10.2 450% Example 3 5 11.4 483% Comparative Example 1 3 7.4 201% Comparative Example 2 1 3.2 102% Comparative Example 3 1.5 4.6 140%

[0109] Table 2:

[0110] Example Pressure bearing capacity / MPa Tensile breaking stress / kPa Healing rateθ Example 1 5.5 12.6 547% Example 2 4 9.4 488% Example 3 4 10.1 501% Comparative Example 1 2 5.2 184% Comparative Example 2 0.5 2.1 83% Comparative Example 3 1 3.3 117%

[0111] It can be seen from the test results of Table 1 and Table 2 that the self-repairing plugging materials prepared in Examples 1 to 3 are suitable for high temperature environments, and the highest temperature resistance temperature can reach 150°C, that is, at 150°C, the pressure bearing capacity is ≥4MPa, the tensile fracture stress is ≥9.4KPa, and the healing rate is ≥488%, which has excellent plugging performance and mechanical properties; compared with the test results at 120°C, the performance of the self-repairing plugging material of the present application at 150°C is as follows: although the tensile fracture stress and the pressure bearing strength are slightly reduced after the temperature is increased, the healing rate is still increasing; this is because the degree of association of the polymer is reduced, and at the same time the molecular chain mobility is increased, so that the polymer chains on the surface of the mutually independent gel can diffuse more easily from one side to the other side, thereby promoting the self-repair process, so the healing rate is improved; and the slight decrease in tensile fracture stress and pressure bearing capacity indicates that the effect of increasing temperature on the molecular structure of the self-repairing gel is weak, that is, the performance of the self-repairing gel of the present application remains basically stable at 120°C to 150°C. In addition, different types of nanoparticles are modified to prepare plugging materials, and different hydrophobic monomers are introduced into copolymers to prepare plugging materials, which will affect the performance of the plugging materials and can be used to fine-tune product performance.

[0112] Specifically, the plugging material of Comparative Example 1 is uniformly dispersed with ordinary nano-silica particles, while the plugging material of Comparative Example 2 is not added with modified nano-silica particles. Compared with the plugging material of Example 1 in which modified nano-silica particles are uniformly dispersed, it can be seen that the tensile fracture stress and the pressure bearing capacity of the plugging material are the lowest compared with those without adding nano-particles; and when ordinary nano-silica particles are added, although the tensile fracture stress and the pressure bearing capacity of the plugging material are increased, the improvement effect is small; and when modified nano-silica particles are added, the tensile fracture stress and the pressure bearing capacity of the plugging material are significantly improved. This is because the surface of the modified nano-particles has abundant cations, which can act on the carboxyl connection of the polymer chain through electrostatic action. At the same time, the modified nano-particles also effectively ensure the stability of the sample at high temperature, thereby greatly enhancing the mechanical properties of the material.

[0113] Compared with Example 1, the difference between Comparative Example 3 and Example 1 is that there is no hydrophobic monomer in the copolymer monomer composition of the plugging material of Comparative Example 3, while the copolymer monomer composition of the plugging material of Example 1 also contains a hydrophobic monomer; it can be seen from the performance of the plugging materials of the two that the introduction of the hydrophobic monomer has a greater impact on the tensile fracture stress of the plugging material, because the hydrophobic association is an important physical effect of the self-repairing of the self-repairing gel, and the lack of hydrophobic monomers will cause the self-repairing efficiency of the sample to be greatly reduced. The hydrophobic groups spontaneously aggregate to form hydrophobic association micro-regions as dynamic cross-linking points, forming a three-dimensional network structure; therefore, when the hydrogel is stimulated by external forces, the micelles tightly entangled by the hydrophobic segments act as dynamic cross-linking points, dispersing stress while preventing the gel from breaking; on the other hand, the hydrophobic segments can dissipate a large amount of energy by disentanglement and slippage, and these effective energy dissipation mechanisms significantly improve the mechanical strength of the gel.

[0114] In summary, the self-repairing gel plugging agent of the present application has excellent self-repairing performance and has a high pressure bearing capacity both before and after self-repairing.

Claims

1. A nanoparticle-doped self-repairing hydrogel plugging material, characterized in that: The modified nanoparticles are uniformly dispersed in a gel-type hydrophobic associating polymer; wherein, The modified nanoparticles are formed by modifying the nanoparticles with acidified 3-aminopropyltriethoxysilane, and the nanoparticles are at least one of nano-alumina powder, nano-silicon oxide powder, nano-magnesium oxide powder, nano-zirconium oxide powder and hydrotalcite; The gel-type hydrophobic associating polymer is copolymerized by a hydrophobic monomer, acrylic acid and acrylamide monomer dissolved in a mixed solvent; the hydrophobic monomer is at least one of lauryl methacrylate, dodecyl methacrylate, hexadecyl methacrylate, octadecyl methacrylate and methyl methacrylate; the acrylamide monomer is at least one of acrylamide and N,N-dimethylbisacrylamide; the mixed solvent is composed of a sodium chloride solution and a surfactant; the surfactant is sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium tetradecyl sulfate, sodium dodecylbenzene sulfonate , at least one of octadecyltrimethylammonium bromide; the sodium chloride aqueous solution is prepared from sodium chloride and water in a weight ratio of (1-2):35; the weight ratio of the surfactant to the water in the sodium chloride solution is (1-2):18, the weight ratio of the hydrophobic monomer to the water in the sodium chloride solution is (1-3):70, the weight ratio of acrylic acid to the water in the sodium chloride solution is (1-2):70, the weight ratio of the acrylamide monomer to the water in the sodium chloride solution is (1.5-2.5):7, and the weight ratio of the modified nanoparticles to the water in the sodium chloride solution is (2-8):

70.

2. A method for preparing the nanoparticle-doped self-repairing hydrogel plugging material according to claim 1, characterized in that: Here are the steps: S1, dispersing 3-aminopropyltriethoxysilane in a mixed solution of ethanol and hydrochloric acid to obtain a dispersion I; S2, filtering the dispersion I and drying the obtained solid to obtain a solid powder; S3, dispersing the nanoparticles in a mixed solution of ethanol and water to obtain a dispersion II; S4, slowly adding the solid powder to the dispersion II, and stirring the reaction at 40°C to 80°C for 6h to 10h to obtain a dispersion III; S5, centrifuging the dispersion III, washing the obtained solid with a low boiling point solvent, and drying it to obtain modified nanoparticles; S6, prepare sodium chloride aqueous solution; S7, dissolving the surfactant, the hydrophobic monomer, the acrylic acid and the acrylamide monomer in a sodium chloride aqueous solution to obtain a monomer mixture; S8, uniformly dispersing the modified nanoparticles in the monomer mixture to obtain a suspension; S9, under an inert atmosphere, adding a catalyst to the suspension, and allowing the suspension to react at room temperature to 60° C. for 2 h to 6 h to obtain a self-healing gel base material; S10, vacuum drying and crushing the self-repairing hydrogel base material to obtain the nanoparticle-doped self-repairing hydrogel plugging material.

3. The preparation method according to claim 2, characterized in that: In step S1, a mixed solution of ethanol and hydrochloric acid is prepared by uniformly mixing ethanol in a weight ratio of 100:1 and 37.5 wt.% of dilute hydrochloric acid; a weight ratio of 3-aminopropyltriethoxysilane to the mixed solution is (10-40):

100.

4. The preparation method according to claim 2, characterized in that: In step S2, the obtained solid is placed at 50°C to 80°C and dried for 12h to 24h.

5. The preparation method according to claim 2, characterized in that: In step S3, the mixed solution of ethanol and water is formed by uniformly mixing ethanol and water in a weight ratio of (1-2):1; the weight ratio of the nanoparticles to the mixed solution is (0.5-2):

20.

6. The preparation method according to claim 2, characterized in that: In step S4, the weight ratio of solid powder I to dispersion liquid II is (10-30):

100.

7. The preparation method according to claim 2, characterized in that: In step S5, the low boiling point solvent is at least one of acetone, ethanol and methanol; the drying temperature is adjusted to 50° C. to 80° C., and the drying time is 12 h to 24 h.

8. The preparation method according to claim 2, characterized in that: In step S6, the sodium chloride aqueous solution is prepared from sodium chloride and water in a weight ratio of (1-2):

35.

9. The preparation method according to claim 2, characterized in that: In step S9, an inert atmosphere is formed by introducing an inert gas into the suspension at a gas flow rate of 20 mL / min to 40 mL / min for 10 min to 30 min; the inert gas is at least one of nitrogen, helium, neon, and argon.

10. The preparation method according to claim 2, characterized in that: In step S10, the vacuum degree of vacuum drying is 0.05 MPa to 0.08 MPa, the drying temperature is 40° C. to 50° C., and the drying time is 24 h to 48 h.

Citation Information

Patent Citations

  • Preparation method of bi-physically-crosslinked self-repairing hydrogel

    CN106432597A

  • Hybrid gel particle while drilling plugging agent and preparation method thereof

    CN110760296A

  • Novel hydrophobic association plugging agent as well as preparation method and application thereof

    CN112794946A

  • Organic-inorganic nano composite hydrogel and water-based drilling fluid

    CN113403042A

  • Supramolecular gel plugging agent for fractured formation as well as preparation method and application of supramolecular gel plugging agent

    CN114507515A

Cited By

  • Functionalized liquid metal-based temperature response type hydrogel material and preparation method thereof

    CN120574362A